ANALISIS PERILAKU NASABAH DALAM BERINVESTASI EMAS DI PEGADAIAN SYARIAH UPS MANGGIS KEC. MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI - Putri Rahma Yenti; Khadijah Nurani (BORJUIS: JURNAL OF ECONOMY, 2025)
This research aims to provide a comprehensive description of customer attitudes in funding gold at Pegadaian Syariah UPS Manggis, Mandiangin Koto Selayan District, Bukittinggi City and help improve the quality of services provided. This research uses a qualitative method in the form of field research, which cites information directly from the research location. The information collection method used is primary information obtained from the results of questions and answers and monitoring, and inferior information obtained from documents related to the research subject. The results of the research prove that important aspects that influence customer attitudes in funding gold at Pegadaian Syariah UPS Manggis are trust in the institution, security of investment, and expected profits. Trust in Pegadaian Syariah as a reliable and comfortable institution is a very powerful aspect. Not only that, ease of access to services and transparent data also support customer decisions in funding gold. Customer attitudes in funding gold are influenced by demographic aspects such as age, education, and income. Older, more intelligent customers with higher incomes tend to be more active in investing in gold.